Flow Mediated Dilation and Its Correlation with Coronary and Systemic Atherosclerosis in Patients Scheduled for Surgical Myocardial Revascularization - Boieriu AM; Luca CD; Tint D (Research Reports in Clinical Cardiology)
Alexandra Maria Boieriu,1,2 Cezar Dumitrel Luca,1,3 Diana Tint1,4 1Faculty of Medicine, “Transylvania” University, Braşov, Romania; 2Cardiology Department, County Emergency Hospital, Braşov, Romania; 3Cardiology Department, Cardiovascular Rehabilitation Hospital, Covasna, Romania; 4Cardiology Department, ICCO Clinics, Braşov, RomaniaCorrespondence: Alexandra Maria Boieriu, Faculty of Medicine, “Transylvania” University, Eroilorst, Nr 29, Braşov, 500036, Romania, Email crisanalexandramaria@yahoo.comPurpose: The study aimed to evaluate endothelial dysfunction (ED), assessed through flow mediated dilation (FMD), in individuals with severe coronary artery disease (CAD) scheduled for coronary artery bypass graft surgery (CABG). Additionally, we examined the association between the severity of EDevaluated throughFMD and the extent of atherosclerosis at the coronary arteries level (SYNTAX I score), carotid arteries and peripheral arteries.Methods: The study included 84 participants recruited between January 2020 and June 2021. Doppler ultrasonography was used to assess both FMD and the degree of carotid artery stenosis. SYNTAX I score was calculated based on coronary angiography, and peripheral artery disease (PAD) was evaluated using computed tomography.Results: FMD was used as a surrogate for assessing ED. We found no statistical difference between men and women [4.46 (1.03– 6.75) in women versus 2.55 (0.95– 6.13 in men; p=0.21). A significant association was observed between FMD and SYNTAX score (p < 0.001). A lower FMD corresponded to a higher SYNTAX score, reflecting an extensive burden of coronary atherosclerosis. Furthermore, ED, as measured by FMD, was indicative of carotid atherosclerosis and PAD, as evidenced by lower FMD in patients with severe carotid plaques (p < 0.001) and severe PAD (p < 0.01).Conclusion: FMD might be a reliable tool to assess systemic atherosclerosis, ED in the brachial artery being related to carotid artery plaque, CAD and peripheral lower limb ischemia.Keywords: flow mediated dilation, SYNTAX I score, carotid stenosis, peripheral artery disease, coronary artery by-pass graft, coronary artery disease